Challenges of building surveying profession in construction industry / Shamnor Syaza Dania Badrol Hisham - Badrol Hisham, Shamnor Syaza Dania (Faculty of Architecture , Planning and Surveying, 2015)
Building survey is a wide-ranging inspection of a property and the most comprehensive of the survey available for residential properties and will provide a detailed evaluation of a property’s condition. However, in Malaysia the potential of building surveying job opportunities in building construction industry is still insignificant. One of the challenges is the lack of a specific governing the BS practice. There is a need to identify the stakeholders view on the issues related to building surveying challenges but there is limited information. The aim of the research is to examine awareness and knowledge on building surveying among the construction stakeholders in order to identify the challenges of building surveyor in construction industry. The first objective is to examine awareness and knowledge on building surveying among the construction stakeholders.The second objective is to identify the challenges of building surveyor in construction industry. The research was carried out using literature search and questionnaire survey to construction stakeholders. 120 responses were obtained and analysed. Findings revealed that the knowledge and awareness among respondents about building surveying are still low despite answering positively on the survey. However, majority agreed that there are many job opportunities for BS graduates in construction industry.Respondents opined BS graduates must learn more about the construction industries and to undergo more training.